There are n polynomials ( P 1 ( x ) . . . . . P n ( x ) ) satisfying the following two equations:
8 ⋅ P ( x ) P ( 0 ) = ( P ′ ( x ) ) 2 ⋅ P ′ ′ ( x ) = 4 .
Find the value of i = 1 ∑ n P i ( 1 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Note that the first line is true only for k ≥ 2 . The cases of k = − ∞ , 0 , 1 need to be dealt with separately. (This is an easy fix.)
For example, if we did not have the requirement that P ( 0 ) = 4 , then P ( x ) = 0 would be another solution.
ohhh! , i thought the degrees o f two polynimials can't be equal !!! ...... kept enterin 9 and 1!!
how u get the value of b.......and how u know the coeficient of x in p2 is -4
Log in to reply
We substitute in the first equation. Then each side of the equation is a polynimial. The two polynomials must be equal so their coefficients have to be equal.
You solve a 3x3 system of equations to find abc. And from the solution b can be either 4 or -4
To the attention of all #Calvin The question when posed should avoid ambiguities . If the question was " There are n distinct polynomials", it would have been litle more appreciated.
A small note: the problem should actually state that the polynomials must have real coefficients. Otherwise, there are also solutions P ( x ) = − x 2 ± 4 i x + 4 , giving ∑ P i ( 1 ) = 1 6 .
A very valid and interesting point that drastically changes the result. Nice find.
Problem Loading...
Note Loading...
Set Loading...
P ( x ) is an k degree polynomial. P ′ ( x ) is an k − 1 degree polynomial. P ′ ′ ( x ) is an k − 2 degree polynomial.
So we get from the first equation k = 2 ⋅ ( k − 1 ) + ( k − 2 )
The above equation gives us k = 2
So, P ( x ) = a ⋅ x 2 + b ⋅ x + c
But P ( 0 ) = 4
so, c = 4
Substituting
P ( x ) = a ⋅ x 2 + b ⋅ x + 4
P ′ ( x ) = a ⋅ 2 ⋅ x + b
P ′ ′ ( x ) = a ⋅ 2
We get
P 1 ( x ) = x 2 + 4 ⋅ x + 4
P 2 ( x ) = x 2 − 4 ⋅ x + 4
So, P 1 ( 1 ) + P 2 ( 1 ) = 1 0